6000 Amazing Facts - Miles Kelly (Essex Miles Kelly, 2018)
This book is jam packed with amazing photographs and illustrations and hard-to-believe facts about the world. Covering topics from history to science, dinosaurs to animal life and key subject areas in between. Along with fun activities, including mini projects and quizzes, these great-value children s books let kids test their knowledge or learn something new!